An efficient distributed fault-tolerant protocol for dynamic channel allocation - Huang, Tingxue; Boukerche, Azzedine; Abrougui, Kaouther; Williams, Jeff (Wireless communications and mobile computing, 2008)
Recent demand for mobile telephone services has been growing rapidly while the electromagnetic spectrum of frequencies allocated for this purpose remains limited. Any solution to the channel assignment problem is subject to this limitation, as well as the interference constraint between adjacent channels in the spectrum. The early research focused on the fixed channel allocation and centralized schemes. Recently, distributed channel allocation schemes have received much attention because of their high reliability and scalability. In these schemes, a base station (BS) has to consult with its neighboring BSs in order to assign a channel to a call. If it cannot communicate with its neighbors, it fails in allocating a channel. However, it is a common phenomenon that a BS fails in communicating with its neighboring BSs due to some reasons, such as heavy traffic load. In this paper, we propose a distributed fault‐tolerant channel allocation schemes which can work well under the mobile host (MH) failures, BS failures, and communication link failures. This algorithm is based upon the mutual exclusion model where the channels are grouped into three equal sized groups and each group of channels cannot be shared concurrently within the same cluster. We prove its correctness. We also report our algorithm's performance with several channel systems using different types of call arrival pattern through comparing with a popular generic distributed algorithm for channel allocation DDRA. Copyright © 2008 John Wiley & Sons, Ltd.